Neutrinos And Large Scale Structures - Dhungel, PR; Sharma, SK; Khanal, U (Scientific World, 2010)
We have summarized the neutrino masses detected/predicted from different sources so far and calculated the Jeans masses of the neutrino structures for these values of neutrino masses. The size of the pure neutrino structures has come to be bigger than the superclusters and great attractor formed around ‘recombination epoch'. Key Words: Neutrino; Large-scale structures; Jeans mass; Relic neutrino; Supercluster; Recombination epoch. DOI: 10.3126/sw.v6i6.2624 Scientific World, Vol. 6, No. 6, July 2008 1-3